The Effect Of Green Training On Corporate Sustainable Performance With Green Transformational Leadership As a Moderating Variable At PT. Angkasa Pura Indonesia, Pekanbaru City Branch Office - Galih Vidia Anggreani; Kurniawaty Fitri; Mida Aprilina Tarigan (Jurnal Bisnis dan Manajemen West Science, 2025)
This study aims to analyze the effect of green training on corporate sustainable performance, as well as the role of green transformational leadership as a moderating variable at PT. Angkasa Pura Indonesia Pekanbaru Branch Office. This study uses a quantitative approach with a questionnaire distribution method. The population in this study are employees at PT. Angkasa Pura Indonesia Pekanbaru Branch Office, with a sampling technique using Proportional Stratified Random Sampling. The data were analyzed using a moderation regression test with the help of SPSS 27. The results showed that green training had a partial positive and significant effect on corporate sustainable performance. In addition, green transformational leadership was proven to moderate this effect.